Ability of Phosphate-Solubilizing Bacteria to Enhance the Growth of Rice in Phosphorus-Deficient Soils - Phringpaen, Waranya; Aiedhet, Wanthakarn; Thitithanakul , Suraphon; Kanjanasopa, Duangkhaetita (Trends in Sciences, 2023)
Phosphate solubilizing bacteria (PSB) are promising candidates for microbiological treatment to improve phosphorus-deficient or P-deficient soil. We have experimentally studied the growth promoting effects of PSBs on rice in P-deficient conditions. The 6 PSBs isolated from rhizosphere soil were identified by 16S rDNA sequencing as Enterobacter asburiae 30FPSSB1, E. mori NTTC11, Priestia aryabhattai KNB6, P. aryabhattai 49KNA2, P. megaterium 65KNA2, and Bacillus sp. 38DFWA. They exhibited plant growth promoting traits via phosphate solubilization and indole acetic acid (IAA) production respectively ranging within 32 - 42 mg/L and 5.3 - 340 mg/L. All the strains produced a large amount of siderophores, and some presented a broad range of antifungal activities reducing the growth of phytopathogens by 10 - 35 %. The effects of bacterial population on rice rhizosphere were evaluated on nutrient agar. Rhizobacterial treatments at high 105 - 108 CFU/mL concentrations inhibited plant growth in IAA dose dependent manner, but such effect diminished at low bacterial titers. The capacity of rhizobacteria to promote plant development under scarcity of P was investigated in pot experiments. Under axenic conditions, Bacillus and Priestia species promoted plant growth, whereas Enterobacter species suppressed it. Plants treated with Bacillus sp. 38DFWA, P. aryabhattai KNB6, and P. megaterium 65KNA2 had increased biomasses of shoots (by 33, 26 and 23 %, respectively) and roots (by 34, 48 and 48 %), which facilitated P availability and increased nutrient uptake in the plant tissues by 89, 96 and 143 %, when the inoculated plants were cultivated in insoluble P (tri-calcium phosphate, TCP) medium. In available P and TCP soil treatments, P. aryabhattai KNB6 and E. mori NTTC11 greatly increased rice plant biomass and gave the highest P accumulation in plant tissues. Interestingly, P. aryabhattai KNB6 strongly increased P uptake in plant tissue by 121 % and promoted rice growth by 22 % in P-deficient soil. This clearly demonstrates that P. aryabhattai KNB6 has great potential for use as a bio-inoculant, and is an attractive alternative to phosphate fertilizers. HIGHLIGHTS In this paper, we report on the potential use of phosphate-solubilizing bacteria as bio-fertilizers in P-deficient soils. The isolated strains of phosphate solubilizing bacteria displayed plant growth promoting traits. Some strains effectively promoted the growth of rice plants cultivated in vitro under restricted available phosphorus (P), increasing shoot and root masses respectively by 23 - 33 and 34 - 48 %, and increasing the accumulation of P in plant tissues by 89 - 143 %. In treatment of soil deficient in P, soluble P, or insoluble P, P. aryabhattai strain KNB6 effectively stimulated plant growth with respective increases by 22, 63 and 128 % compared to the control, through increasing P solubility, P uptake, and promotion of root development. GRAPHICAL ABSTRACT